Gambaran Histopatologi dan Populasi Bakteri Asam Laktat pada Duodenum Ayam Pedaging yang Diberi Sinbiotik dan Diinfeksi Escherichia coli (HISTOPATHOLOGY AND LACTIC ACID BACTERIA POPULATION IN DUODENUM WITH SINBIOTIC AND ESCHERICHIA COLI INFECTED BROILER - Daud, Muhammad; Yaman, Muhammad Aman; Zulfan, Zulfan (Jurnal Veteriner; Vol 20 No 3 (2019), 2019)
The research aims to study the use of synbiotics as feed additives in rations on describe lesions histopathology and population of lactic acid bacteria in duodenum infected with Escherichia coli. The study used 96 broiler Jumbo series A Cibadak strains which were maintained until the age of six weeks. The study was conducted by experimental method, using a completely randomized design (CRD) with eight treatments of rations and four replications. The broilers were devided into eight treatment diets: R1 (basal diet/control), R2 (basal diet + prebiotic 0.4%); R3 (basal diet + probiotic 108 CFU); R4 (basal diet + prebiotic 0.4% + probiotic 108 CFU); R5 (basal diet + infected with E. coli 104 CFU); R6 (basal diet + prebiotic 0.4% + infected with E. coli 104 CFU); R7 (basal diet + probiotic 108 CFU + infected with E. coli 104 CFU); and R8 (basal diet + prebiotic 0.4% + probiotic 108 CFU + infected with E. coli 104 CFU). The observed variables were histopathology based on lesio microscopic and lactic acid bacteria population in duodenum age 2, 4 and 6 weeks. Data was analyzed by using one-way analysis of variance then continued with Duncan test. The results showed that the use of probiotics, prebiotics and synbiotics significantly (P<0.05) decreased histopathological lesio score and increased the population of lactic acid bacteria in duodenum age 2, 4 and 6 weeks. In conclusion the use of synbiotics as feed additives in the ration a positive on describe lesions histopathological and increase in the population of lactic acid bacteria in duodenum age 2, 4 and 6 weeks infected and not infected with E. coli.